Molecular biology of human DDX49 - novel biochemical activities - Anandavijayan, Sabesan (2023)
DExD-box helicases belong to superfamily II of RNA helicases and are characterised by a conserved Asp-Glu-X-Asp motif in their primary protein sequence. These helicases are often involved in pre-mRNA splicing, ribosome biogenesis and also cell cycle mediation; as such, they are implicated in the oncogenesis and proliferation of various cancer types. The overexpression of DEAD-box protein 49 (DDX49) has been associated with a favourable prognosis in cervical cancer patients, however, its structure and function has yet to be fully elucidated. We report that DDX49 is a dual function helicase and nuclease, and discuss how CRISPR-Cas9 mediated downregulation of DDX49 may affect the proliferation and viability of U2OS osteosarcoma cells.